Optimization of Growth Conditions to Produce Sustainable Polyhydroxyalkanoate Bioplastic by Pseudomonas aeruginosa EO1 - Mahato, Richa Prasad; Kumar, Saurabh; Singh, Padma (Frontiers in Microbiology, 2021)
Polyhydroxyalkanoates (PHAs) are intracellularly synthesized by bacteria as carbonosomes that exhibit biodegradable thermoplastics, elastomeric properties. The use of cheaper edible oils as a source of carbon assists in the reduction of such biopolyesters production cost. In this work, different edible oils such as groundnut oil, mustard oil, sesame oil, soybean oil were used to check their effect on PHA production from Pseudomonas aeruginosa EO1 (MK049902). Pseudomonas aeruginosa EO1 was used in a two-stage production system. In the first stage, bacterial growth was favoured and, in the second, PHA was synthesized. Groundnut oil (GNO) was found as a best carbon source for polyhydroxyalkanoate (PHA) production. The use of 2% (v/v) GNO, rich in saturated fatty acids, allowed PHA content of 58.41% and dry cell weight (DCW) of 10.5 g/L at pH7 and temperature 35°C for 72 h. Groundnut has a high potential for oil production and for diversification of co-products with some potential of value aggregation. Such a perennial and sustainable species will almost certainly meet the criteria for becoming a significant commercial oilseed crop. Fourier transform infrared spectroscopy (FTIR) spectra showed strong characteristic bands at 1282, 1725, 2935, 2999, and 3137 cm-1 for the PHA polymer. Gas chromatography-mass spectrometry (GC-MS) detects the presence of PHA copolymers.